Die schwarze Perle - O'Dell, Scott 1898-1989 (Dt. Taschenbuch-Verl., 1988)
In claiming as his own the magnificent black pearl he finds, a sixteen-year-old youth enrages the sea devil who legend says is its owner.
EST: The black pearl <dt.>
Keywords: Pearl diving -- Fiction; Pearl diving -- Juvenile fiction; Baja California (Mexico : Peninsula) -- Fiction; Baja California (Mexico : Peninsula) -- Juvenile fiction